Slide tracheoplasty outcomes in children with congenital pulmonary malformations. (15th November 2016) - DeMarcantonio, Michael A.; Hart, Catherine K.; Yang, Christina J.; Tabangin, Meredith; Rutter, Michael J.; Bryant, Roosevelt; Manning, Peter B.; de Alarcón, Alessandro
Abstract : Objectives/Hypothesis: Evaluate and compare surgical outcomes of slide tracheoplasty for the treatment of congenital tracheal stenosis in children with and without pulmonary malformations. Study Design: Retrospective chart review at a tertiary care pediatric medical center. Methods: We identified patients with tracheal stenosis who underwent slide tracheoplasty from 2001 to 2014, and a subset of these patients who were diagnosed with congenital pulmonary malformations. Hospital course and preoperative and postoperative complications were recorded. Results: One hundred thirty patients (18 with pulmonary malformations, 112 with normal pulmonary anatomy) were included. Pulmonary malformations included unilateral pulmonary agenesis (61%) and hypoplasia (39%). Children with pulmonary malformations had a greater median age compared to their normal lung anatomy counterparts. Preoperatively, patients with pulmonary malformations more frequently required preoperative mechanical ventilation (55.6% vs. 21.3%, P = .007), extracorporeal membrane oxygenation (ECMO) (11% vs. 0.9%, P = .05), and tracheostomy (22.2% vs. 3.6%, P = .01). Postoperatively, patients with pulmonary malformations more frequently required mechanical ventilation >48 hours (78% vs. 37%, P =.005) and ECMO use (11% vs. 0.9%, P = .05). Pulmonary malformation patients and children with normal anatomy did not differ in terms of postoperative tracheostomy (16.7% vs. 4.4%, P > .05), dehiscence (6% vs. 0%, P > .05%), restenosis (11% vs. 6%, P > .05) or postoperative figure 8 deformity (6% vs. 3%, P > .05). Mortality, however, was significantly increased (22.2% vs. 3.6%, P = .01) in children with pulmonary malformations. Conclusions: Although slide tracheoplasty can be successfully performed in patients with abnormal pulmonary anatomy, surgeons and families should anticipate a more difficult postoperative course, with possible associated prolonged mechanical ventilation, ECMO use, and higher mortality than in children with tracheal stenosis alone. Level of Evidence: 4. Laryngoscope, 127:1283–1287, 2017